Instrumental or Normative Motives: How Should Brands Implement Their Activism Campaigns? - Lécuyer, Charlotte (Journal of business ethics, 2026)
To reveal the processes that underlie the effects of brand activism campaigns, this article reports on three studies that examine why brand activism may generate negative responses from consumers. Drawing on attribution theory and agenda-setting theory, a first experiment reveals that consumers associate brand activism campaigns with either instrumental or normative corporate motives. Perceptions of instrumental (normative) motives influence consumers’ responses negatively (positively). A second experiment clarifies that brands that quickly take a stand on sociopolitical issues after specific events appear less instrumental and evoke positive purchase intentions. This effect is especially strong if the issues have not attracted much media coverage. A third experiment proposes concrete time frames for efficient brand activism campaigns. Finally, the research provides marketing managers with advice on how to benefit from brand activism advertising.